Tampilan Produksi dan Efek Imunomodulasi Ayam Broiler yang Diberi Ransum Berbasis Wheat Pollard Terolah (PRODUCTION PERFORMANCE AND IMMUNOMODULATION EFFECTS ON BROILER GIVEN A PROCESSED WHEAT POLLARD BASED DIET) - Sulistiyanto, Bambang; Kismiati, Sri; Utama, Cahya Setya (Jurnal Veteriner; Vol 20 No 3 (2019), 2019)
An immunomodulator is a natural body defence mechanism due to the stimulation of objects/ environments, both specific and non-specific by means of cellular and humoraldefence. The objective of the study was to prove the immunomodulation ability of broiler chickens up to age 35 days that dietary fed various wheat pollard based rations. The design used in the study was a complete randomized design with six treatments and three replications. The treatment of broiler rats consisted of BR-IAJ (T0), control feed with wheat pollard base (T1), control feed with wheat pollard base plus probiotic (T2), wheat pollard based feed steamed (T3), fermented wheat pollard based feed 40% (T4 ) and fermented wheat pollard based feed 60% (T5). The rations used contained 20,5-22,5% protein with 2900-3100 Kcal metabolic energy. Lohman MB 202 Platinum from PT. Japfa Comfeed used in research with average day old chick (DOC) weight of 36,39 + 2,45 g. Parameters observed included body weight, feed intake, feed conversion ratio (FCR), relative weights of liver organ, thymus, lymph and bursa fabricius. The results showed that wheat pollard-based rations had a significant effect (p <0,05) on the relative weight of liver organ, body weight, FCR and ration consumption, but did not affect the relative weights of spleen organ, thymus and bursa fabricius. The mean relative weight of consecutive liver as follows: 2,47 g (T0), 2,83 g (T1), 3,40 g (T2), 2,99 g (T3), 3,15 g (T4) and 3,06 g (T5). The average body weight, consumption and FCR rations were as follows: 1415,24 g; 136,45 g/day; 2,03 (T0), 775,04 g; 125,19 g/day; 3,40 (T1), 813,17 g; 129,86 g / day; 3,36 (T2), 792,89 g; 128,14 g /day; 3,54 (T3), 892,91 g; 138,33 g /day; 3,27 (T4), 969,56 g; 155,52 g/day; 3,37 (T5). The conclusion of the study was that the ration with the addition of wheat pollard 60% was able to provide an increase in body weight gain and the best immunomodulation seen from the aspect of the proportion of immunomodulating organs to the growth of broiler chickens.